Sintesis dan Karakterisasi Nanopartikel Perak – Ekstrak Daun Pelawan (Tristaniopsis Merguensis Griff) Termodifikasi PVA - Ike Nur Amanah; Della Puspita Indriyani; Bana Prilia Muharomah; Verry Andre Fabiani (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
Synthesis and characterization of silver nanoparticles have been carried out by reacting pelawan leaf extract (Tristaniopsis Merguensis Griff) with a solution of 0.05 M silver nitrate (AgNO3) and PVA through a stirring process for 24 hours. UV-VIS, and XRD analyzed the characteristics of silver nanoparticles. Gray and accompanied by a precipitate. The results of UV-VIS analysis showed absorption at a wavelength of 420 at a concentration of 0.75% and 460 nm at a concentration of 3%. XRD diffractogram of PVA modified silver nanoparticles showed a diffraction pattern of %) and 2 = 38.25o, 44.43o, 64.43o, 77.43o (3% PVA) with Miller indices (111), (200), (220), and (311). Based on the results of an (International Center For Diffaction Data) No. 01- 071-4613, namely at 2 38.11, 44.2, 64.37 and 77.42 (PVA 0.75), silver nanoparticles with a cubic crystal system were formed. In addition, the results of the XRD analysis are also used to determine the average nanosilver particle size using the Debye-Scherr equation.